2016
DOI: 10.5296/jas.v4i3.9925
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Competitiveness of the Swaziland Sugar Industry

Abstract: The issue of abolishment of trade agreements preferences pose a great threat to the sugar industry in Swaziland. Using both the Relative Trade Advantage and Porter`s 1990 National Diamond concept, the major objective of the study was to examine the comparative advantage of the sugar industry in the global market with the aim of establishing the contributing factors and constraints to the competitiveness of the Swaziland sugar industry. The Relative Trade Advantage (RTA) method developed by Balassa was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As noted by Ngcobo and Jewitt (2017), this can be attributed to inflows of FDI and its role in technological spillovers, increased investment in infrastructure and adoption of efficient methods of production, which in turn can enhance a country's competitiveness in the sugar export market. This observation is also supported by Nyanzunda (2012) who further opines that that technological advancements that come with FDI increase productivity, enhance access to markets with high returns and play a pivotal role in determining the competitiveness of the sugar industry. Sugar production is a capitalintensive business venture that needs investments to maintain a given level of competitiveness (Galović and Bezić, 2019).…”
Section: Overview Of Africa's Sugar Exportsmentioning
confidence: 73%
See 1 more Smart Citation
“…As noted by Ngcobo and Jewitt (2017), this can be attributed to inflows of FDI and its role in technological spillovers, increased investment in infrastructure and adoption of efficient methods of production, which in turn can enhance a country's competitiveness in the sugar export market. This observation is also supported by Nyanzunda (2012) who further opines that that technological advancements that come with FDI increase productivity, enhance access to markets with high returns and play a pivotal role in determining the competitiveness of the sugar industry. Sugar production is a capitalintensive business venture that needs investments to maintain a given level of competitiveness (Galović and Bezić, 2019).…”
Section: Overview Of Africa's Sugar Exportsmentioning
confidence: 73%
“…For instance, most African countries have a potential to enhance their competitiveness on the international market given their favorable climatic conditions for growing sugar and availability of land and other natural resources (Hess et al, 2016). Additionally, trade barriers, changes in government policies and regulations that enhance productivity can also significantly affect the competitiveness of commodities on the international market (Srivastava et al, 2006;Nyanzunda, 2012;Bouët et al, 2021). These factors can create opportunities or challenges for industries and countries to maintain or improve their comparative advantage in the global market.…”
Section: Overview Of Africa's Sugar Exportsmentioning
confidence: 99%
“…Kitching, Blackburn, Smallbone and Dixon (2009), with a study on firms in the United Kingdom, established that strategic adaptation under challenging times resulted in improved performance. A study by Ndlangamandla (2016) in Swaziland revealed that sugar companies in the country were recording high performance relative to their competitors due to their effectiveness in adapting to the sugar market. A study by Imbambi (2017) on sugar companies in western Kenya also established that technological and material capabilities as part of the companies' strategies resulted in high performance.…”
Section: Introductionmentioning
confidence: 99%